2015
DOI: 10.1038/onc.2015.197
|View full text |Cite
|
Sign up to set email alerts
|

p54nrb/NONO regulates lipid metabolism and breast cancer growth through SREBP-1A

Abstract: Dysregulation of lipid metabolism is common in breast cancer. However, the underlying mechanisms remain elusive and the contribution of aberrant lipid metabolism to the malignant phenotypes of breast cancer is poorly understood. Here, we show that the nuclear protein p54(nrb)/Nono is highly expressed in breast cancer tissues as compared with the adjacent normal tissues in human patients. To determine the functions of p54(nrb) in breast cancer, we performed a biochemical screen and identified SREBP-1a, a master… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…Targeting lipid metabolism and its related regulators have emerged as a promising antitumor strategy. We have previously found that SREBP1‐mediated de novo lipogenesis promotes cancer cell proliferation by providing sufficient lipids (Liu et al ., 2016; Zhu et al ., 2016). Transcription factors require cofactors to help fully activate gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting lipid metabolism and its related regulators have emerged as a promising antitumor strategy. We have previously found that SREBP1‐mediated de novo lipogenesis promotes cancer cell proliferation by providing sufficient lipids (Liu et al ., 2016; Zhu et al ., 2016). Transcription factors require cofactors to help fully activate gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…10,42,43 Because it is involved in a variety of biological processes, including RNA splicing and editing, DNA unwinding and repairing, gene transcription and differentiation of stem cells, NONO(p54 nrb ) has been believed to play an important role in cancer. 42 In fact, p54 nrb has been found to be expressed strongly in prostate cancer 44 and malignant melanoma. 45 The specific features of NONO(p54 nrb ) in these distinctive neoplasms remain poorly understood because of their extreme rarity.…”
Section: Discussionmentioning
confidence: 99%
“…SREBP1 has an important role in cancer progression likely by providing the membrane building materials to support the rapid proliferation of cancer cells [16, 17]. We have utilized several experimental approaches to identify novel SREBP interacting proteins [18, 19]. Here, we presented a novel interaction between the nuclear protein MARVELD1 and the nuclear form of SREBP1.…”
Section: Discussionmentioning
confidence: 99%